Perlakuan akuntansi piutang rekening air pada PDAM Tirta Agara Kabupaten Aceh Tenggara - Shapura, Mutiara Ratu; Juliana Nasution (Program Studi Akuntansi IKOPIN, 2022)
PDAM income is obtained from the distribution of clean water to cosromers on credit.Water receivables are the main income for PDAM,sales activity is one of the most important activities.Thus,the sales department is required to have good sales information to support its performance,be thorough and accurate in the management of sales results as well as the reporting process and supported by adequate data source facilities and facilities. “Accounting for Water Account Receivables at PDAM Tirta AAgara,Southeast Aceh Regency”.